ESTUDIOS SOBRE LAS RESAN LUIS POTOSIUESTAS CONVULSIVANTES EXPERIMENTALES Y SUS MODIFICACIONES I INTRODUCCION Y TECNICA - ARROYO, S; ALVAREZ, JAVIER A; ALCALDE OBRADOR, S (Instituto de Salubridad Publica, CD MEXICO, DF, MEX, 1945)
In the gastrocnemius muscle of the cat during fatigue of contraction produced by an electrical stimulus of low frequency, the amplitude of contractions was diminished by intra-arterial injns of a digitalis compound ("Strophosid," Sandoz) During fatigue
BOL INST ESTUD MED BIOL
Keywords: ESTUDIOS, RESPUESTAS CONVULSIVANTES EXPERIMENTALES, MODIFICACIONES, INTRODUCCION, TECNICA; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; COMPORTAMIENTO ANIMAL